Gastrointestinal stromal tumor in perforated Meckel’s diverticulum: a case report and literature review - Naoki Hashizume; Saki Sakamoto; Suguru Fukahori; Shinji Ishii; Nobuyuki Saikusa; Yoshinori Koga; Naruki Higashidate; Shiori Tsuruhisa; Hirotomo Nakahara; Yoshiaki Tanaka; Minoru Yagi (Surgical Case Reports, 2020)
Abstract Introduction Gastrointestinal stromal tumor (GIST) is rare neoplasms of the gastrointestinal tract associated with high rates of malignant transformation. GIST has been found largely in the stomach, small bowel, colon and rectum, and esophagus, but about 5% are found in other locations. We herein report a 56-year-old woman with a GIST in perforated Meckel's diverticulum. After encountering this patient, a review of the literature found reports of 18 similar patients. Case presentation A 56-year-old woman diagnosed with galactosialidosis (β-galactosidase-neuraminidase deficiency) presented with vomiting. On contrast-enhanced computed tomography, peritonitis due to perforation of the intestine was diagnosed based on the free air and dilated loop of the small bowel. Laparotomy revealed perforation of Meckel’s diverticulitis located 50 cm from the ileocecal valve. Partial resection of the ileum, including the diverticulum, and end-to-end anastomosis of the small intestine were performed. Regarding the pathological findings, the edge of the diverticulum wall consisted of a solid mass measuring 1.0 cm in size, and the tumor cells were spindle-shaped with 1 mitosis present per 50 high-power fields. The diagnosis was established as GIST of the Meckel's diverticulum. The postoperative period was uneventful. Follow-up at two years revealed no evidence of recurrence. Conclusion GIST in perforated Meckel's diverticulum is very rare. The potential for the coexistence of GIST or other tumor should be considered in the treatment of perforated Meckel's diverticulum.